Effect of precursor solution concentrations of PCBM interlayer between low-temperature spin-coating TiO2 electron transport layer and light absorption layer on physical properties of perovskite film and photo-current hysteresis of photo-voltaic devices - Yu, Xing; Zou, Xiaoping; Cheng, Jin; Chen, Dan; Yao, Yujun; Chang, Chuangchuang; Liu, Baoyu; Wang, Junqi; Zhou, Zixiao; Li, Guangdong (Optik (Stuttgart), 2021)
we insert (6,6)-phenyl c61 butyric acid methyl ester (PC61BM) interlayer of different precursor solution concentrations between low-temperature TiO2 electron transport layer (ETL) and light absorption layer to modify charge carrier transporting, mitigate hysteresis and improve perovskite film quality. The results show that the TiO2 / perovskite interface, the perovskite film morphology and photo physical properties can be modified by optimizing the precursor solution concentrations of PC61BM interlayer, which facilitates the electron extraction from perovskite absorption layer to TiO2 ETL and reduces the hysteresis.